2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090913
|View full text |Cite
|
Sign up to set email alerts
|

Classification performance of the frequency-related parameters derived from uterine EMG signals

Abstract: Frequency-related parameters derived from the uterine electromyogram (EMG) signals are widely used in many pregnancy monitoring and preterm delivery prediction studies. Although they are classical parameters, they are well suited for quantifying uterine EMG signals and have many advantages over amplitude-related parameters. The present work aims to compare various frequency-related parameters according to their classification performances (pregnancy vs. labor) using the receiver operating characteristic (ROC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Most studies, including [10], use four electrodes although one study utilizes two [12]. In a series of other studies, sixteen electrodes were used [13][14][15][16][17][18], and a high density grid of 64 small electrodes was used in [19]. The results show that EHG may vary from women to women.…”
Section: Electrohysterographymentioning
confidence: 98%
See 1 more Smart Citation
“…Most studies, including [10], use four electrodes although one study utilizes two [12]. In a series of other studies, sixteen electrodes were used [13][14][15][16][17][18], and a high density grid of 64 small electrodes was used in [19]. The results show that EHG may vary from women to women.…”
Section: Electrohysterographymentioning
confidence: 98%
“…However, for analysis and feature extraction purposes, translation, into other domains, is possible. These include a frequency representation, via Fourier Transform, [16], [29][30][31] and wavelet transform [25], [28], [31][32][33][34]. The advantage of frequency-related parameters is that they are less susceptible to signal quality variations, due to electrode placement or the physical characteristics of the subjects [27].…”
Section: Feature Extraction From Electrohysterography Signalsmentioning
confidence: 99%
“…The k-NN algorithm has been used by Diab et al [15] with an emphasis on Autoregressive (AR) modelling and wavelet transformation pre-processing techniques. The study focused on classifying contractions into three types using data obtained from 16 women.…”
Section: Related Studiesmentioning
confidence: 99%
“…These are spaced at a horizontal, or vertical, distance of 2.5cm to 7cm apart. Most studies use four electrodes, although other configurations have been reported; two (Doret, 2005); 16 (Moslem et al, 2011a(Moslem et al, , 2011b(Moslem et al, , 2011c(Moslem et al, , 2011d2012); and 64 (Rabotti et al, 2010).…”
Section: Electrohysterographymentioning
confidence: 96%